Progress, but at the Expense of Male Power? Institutional Resistance to Gender Equality in an Irish University - Hodgins, M.; O’Connor, P. (Frontiers in Sociology, 2021)
Abstract Gender equality is a whole-organization endeavor. Building on Agócs’ (1997) concept of institutionalized resistance this article undertakes a feminist critique of policy and practice around internal promotions to the equivalent of Associate Professor level in one Irish university (called the Case Study University). This university was selected because of its low proportion of women in senior academic positions. The methodology is a single case study design, employing documentary analysis, including secondary data. Since 2013 the proportion of women at Associate Professor in the Case Study University increased significantly (bringing them close to the national average): this being associated with increased transparency, with the cascade model in the background. However, men’s ‘chances’ have varied little over time and at 1:4 are the highest in Irish universities. This article uses Agócs (1997) stages of institutional resistance to show that while some changes have been made, ongoing institutionalised resistance is reflected in its failure to accept responsibility for change as reflected in its refusal to challenge the ‘core mission’ and restricting the focus to ‘fixing the women’; and its failure to implement change by focusing on ‘busy-ness’ which does not challenge power and colluding with foot-dragging and slippage in key areas. It is suggested that such institutional resistance reflects the enactment of hidden or stealth power. The article implicitly raises questions about the intractability and the covertness of men’s power and privilege and the conditions under which women’s ‘chances’ are allowed to improve, thus providing insights into the extent and nature of institutional resistance.